The elasticity of substitution and the sector bias of International Outsourcing: Solving the puzzle - Daniel Horgos (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2009)
Considering the sector bias of International Outsourcing within a 2x2 framework, four different scenarios appear. Each industry can either relocate its high or its low skill intensive production fragment. Traditionally, depending on the superiority of a wage vs. an outsourcing-effect, general equilibrium effects of two scenarios are assumed to be ambiguous. Applying a formal duality approach and a calibration exercise for the German economy, this contribution shows that a focus on the elasticity of substitution can solve the puzzle. With the elasticity exceeding a critical value, unambiguous results in all four scenarios appear, supporting the sector bias of International Outsourcing.
urn:nbn:de:gbv:705-opus-19193
Keywords: F16; F41; E25; 330; International Outsourcing; Sector Bias; Elasticity of Substitution; Offshoring; Outsourcing; Auslandsproduktion; Sektorale Beschäftigungsstruktur; Hochqualifizierte Arbeitskräfte; Ungelernte Arbeitskräfte; Substitutionselastizität; Theorie; Deutschland